Take us back to the graves of our ancestors! Land as a source and site of conflict in the Gutu District of Zimbabwe, 2000-2016.: Paper presented at Midlands State University International Research Conference held at Zvishavane Campus, 29-30 September 2017 - Tarugarira, Gilbert (Midlands State University, 2017)
Land is a primary and fundamental, highly symbolic resource for the vast majority of African people. It is a core element in the complex social relations of production and reproduction. Being a valuable and immovable resource of limited quantity, its ownership and usage invoke emotional responses which spill into questions of autochthony and identity politics. As this paper demonstrates; how land should be used, owned and controlled and by whom has revealed a highly contested and conflictual terrain in Gutu. The volatile dynamics of conflict have not always conformed to the conventions of logic. Claims over ancestral land in Gutu have also had an impact on people’s identity and their feelings of connectedness with the social and cultural environment in its entirety. However ignoring these complexities has led to tenure reforms which have aggravated land-based conflict. In this paper, I argue that while conflict has been a symptom of persistent inequalities, it has provided an opportunity for the elite to consolidate their holdings of land and valuable resources. The reluctance by the District Administrator’s office to recognize and resolve lingering disputes born of the land and agrarian reform programmes has triggered extended protests and violence, prompting local-level institutions to make fragile and ill-conceived decisions on land ownership. With economic, symbolic and emotional aspects at stake, the Gutu experience is studied to show that while land has been a source of conflict, it remains an essential element in peace building in post-conflict situations.